Ribosomal 18S rRNA base pairs with mRNA during eukaryotic translation initiation - Franck Martin (Nature Portfolio, 2016)
Prokaryotic translation initiation involves mRNA-ribosomal RNA base pairing interactions. Here, the authors provide evidence for a similar base pairing interactions occurring between the human h4 mRNA and helix 16 of the small subunit rRNA to position the correct AUG codon in the decoding site.